Knowledge, Attitude & Practices Regarding Biomedical Waste Management Amongst Nursing Staff of Khaja Banda Nawaz Institute of Medical Sciences, Kalburgi, Karnataka - Indupalli, Amrutha Swati; Motakpalli, Kaviraj; Giri, Purushottam A.; Ahmed, Bendigeri Nazir (National Journal of Community Medicine, 2015)
Context: Globally 18 to 64% of healthcare institutions are reported to have unsatisfactory Bio-Medical Waste Management (BMWM) facili- ties. Objective: To assess the knowledge, attitude and practices regarding biomedical waste management of hospital nursing staff Method: A hospital based cross-sectional study was carried out amongst 100 nursing staff working in Khaja Banda Nawaz Institute of Medical Sciences, Hospital Kalburgi. Result: Majority had knowledge regarding 92% colour coding, 77% sources of bio-medical waste, 75% steps in its management and 68% diseases transmitted through it and 91% had positive attitude to- wards biomedical waste management. Among practices (90%) are using needle hub cutter for needles and syringes and (84%) segrega- tion of bio-medical waste and (81%) following personal protective measures at their work place. Conclusion: The overall knowledge, attitude and practice regarding bio-medical waste management among the study participants were found to be average. Knowledge was poor regarding correct catego- ries of BMW. Only 57% are maintaining bio-medical waste record at their work place. It is recommended to have strict supervision by the administrative personnel and periodical reorientation on biomedical waste management guidelines.